Management of head injury patients in a General Intensive Care Unit (GICU) with no neurosurgical service - M, Melor; S, Ahmad; H, Zaiton; Y, Zolkepli (2001)
Our hospital is a referral hospital for a region having a population of 1.8 million and incidents of motor-vehicle accidents of about 11700 per year. HI patients are managed by the general surgeons who had neurosurgical experience of a variable experience who are in change of the General Intensive Care Unit (GICU)